Kontribusi Interpersonal Trust dan Intimate Friendship terhadap Self Disclosure Generasi Z Pengguna Second Account Instagram - Aulia, Zahra; Dwatra, Free Dirga (TSAQOFAH, 2025)
This study aims to determine the contribution of interpersonal trust and intimate friendship to self-disclosure among Generation Z users of second accounts. This phenomenon indicates that individuals use second accounts as a means of self-expression more openly compared to their main accounts, which tend to be public. The method applied in this study is quantitative with a correlational approach. The sample consists of 302 Generation Z users of second accounts residing in Padang City, using accidental sampling technique. The findings from multiple linear regression analysis show a significant positive contribution between interpersonal trust and intimate friendship to self-disclosure, with a significance value of 0.000 (p < 0.05). An R square value of 0.259 was also obtained, meaning that interpersonal trust and intimate friendship together contribute 25.9% to self-disclosure. The findings indicate that interpersonal trust contributes 10.9% and intimate friendship contributes 15.1% to self-disclosure. Therefore, the higher the level of interpersonal trust and intimate friendship, the greater the likelihood that individuals will experience self-disclosure.